2007
DOI: 10.1007/s10815-006-9094-5
|View full text |Cite
|
Sign up to set email alerts
|

Birth after transfer of frozen-thawed vitrified biopsied blastocysts

Abstract: Purpose: To present a case describing the birth of a healthy female after the replacement of vitrified biopsied embryos after Preimplantation Genetic Diagnosis.Method: A descriptive case report of a single patient.Results: Our patient carrier of an X-linked disease became pregnant and as a result a healthy girl was born.Conclusions: This report shows that blastocysts obtained from biopsied embryos can be successfully cryopreserved by a simple, secure and low-cost vitrification method using a Hemi-straw support. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…With implementation of cryopreservation in IVF cycles, surplus healthy blastocysts can be cryopreserved. If necessary, a second round of transfer can be done when the endometrial condition of the recipients is ready for the transfer (Parriego et al, 2007). Importantly, in this second round of transfer cycle, the uncertainty of having embryo(s) eligible for transfer can be minimized if cryopreservation efficiency is guaranteed.…”
Section: Human-assisted Reproductive Technologiesmentioning
confidence: 99%
“…With implementation of cryopreservation in IVF cycles, surplus healthy blastocysts can be cryopreserved. If necessary, a second round of transfer can be done when the endometrial condition of the recipients is ready for the transfer (Parriego et al, 2007). Importantly, in this second round of transfer cycle, the uncertainty of having embryo(s) eligible for transfer can be minimized if cryopreservation efficiency is guaranteed.…”
Section: Human-assisted Reproductive Technologiesmentioning
confidence: 99%
“…Zheng et al found that vitrification of biopsied cleavage stage embryos resulted in higher survival rate compared to different slow freezing methods [18]. Parriego et al reported the first pregnancy achieved after vitrification of a biopsied cleavage stage embryo for the purposes of PGS [19]. Transferring biopsied cleavage embryos cryopreserved after in vitro culture and blastulation has shown improved results over the immediate transfer at the cleavage stage [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreserving surplus embryos from the first round of the program can now be a backup for the second or more rounds of pregnancy. It can be done simply by transferring the thawed embryos to the recipients when the endometrial conditions are ready (Parriego et al, 2007).…”
Section: Logistic Advancement On Assisted Reproduction Technologiesmentioning
confidence: 99%